2015
DOI: 10.18632/oncotarget.6540
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from bulk and stem cells from human prostate cancer have a differential microRNA content that contributes cooperatively over local and pre-metastatic niche

Abstract: The different prostate cancer (PCa) cell populations (bulk and cancer stem cells, CSCs) release exosomes that contain miRNAs that could modify the local or premetastatic niche. The analysis of the differential expression of miRNAs in exosomes allows evaluating the differential biological effect of both populations on the niche, and the identification of potential biomarkers and therapeutic targets. Five PCa primary cell cultures were established to originate bulk and CSCs cultures. From them, exosomes were pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
125
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(145 citation statements)
references
References 70 publications
2
125
0
3
Order By: Relevance
“…18,19 Cancer-derived exosomes have been found to contribute to TME remodelling and premetastatic niche formation. 20,21 In this study, we have investigated the potential role of exosome vesicles in hypoxia-dependent signalling between lung cancer cells and endothelial cells. Our research reveals that lung cancer cells and endothelial cells communicated by miR-23a released from cancer cells under hypoxic conditions, which may facilitate tumour angiogenesis without directly contacting contiguous tissue.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Cancer-derived exosomes have been found to contribute to TME remodelling and premetastatic niche formation. 20,21 In this study, we have investigated the potential role of exosome vesicles in hypoxia-dependent signalling between lung cancer cells and endothelial cells. Our research reveals that lung cancer cells and endothelial cells communicated by miR-23a released from cancer cells under hypoxic conditions, which may facilitate tumour angiogenesis without directly contacting contiguous tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular vesicles have been shown to modulate numerous factors in tumour cells including proliferation (20), viability (21) and metastatic capability (22). The tumour microenvironment has also been shown to be modulated by EV-mediated communication between the tumour and other cells such as cancer associated fibroblasts (23,24) and mesenchymal stem cells (25). EVs are able to modulate angiogenesis, an important factor in cancer progression (26)(27)(28)(29).…”
mentioning
confidence: 99%
“…In the same study, Kumar et al (66) also demonstrated the ability of breast and prostate CSCs to release exosomes expressing the classical vesicle markers CD63, CD9, CD81, TSG101 and Alix without identifying selective surface molecules for those exosomes; however, antineoplastic treatments can modulate the levels of those markers, enhancing the release of exosomes from CSCs. Interestingly, when the miRNAs from exosomes released from prostate CSCs were compared with those contained in the EVs secreted by the cancer cells, the first population presented groups of differentially-expressed miRNAs associated with tumor progression and pre-metastatic niche formation, thus demonstrating how strongly the initiation of metastasis relies on the release of EVs from CSCs (67). In addition, exosomes released by PCA-initiating cells overexpressing CD44v6 (68) contribute to tumor progression by stimulating non-cancer initiating cells to acquire the CSC phenotype, complemented by the capacity of these exosomes to stimulate in vivo angiogenesis, invasion and host response (69).…”
Section: Evs In Csc Nichementioning
confidence: 99%